Effect of Mercury Administration as an Oxidative Stress Trigger in Hepato-Renal Injuries - Yuliana, Ida; Triawanti; Prenggono, Muhammad Darwin; Oktaviyanti, Ika Kustiyah; Irfan Maulana; Fahrina Ulfah (Universitas Airlangga, 2025)
Introduction: Mercury as the source of free radicals can trigger the activation of oxidative stress pathways. With its high toxicity, it can cause hepato-renal injuries. There have been many studies on mercury toxicity in various organs, but there are still few scientific studies that examine the hepato-renal injuries caused by mercury through the oxidative stress pathway. This study was conducted to investigate the triggering of the oxidative stress pathway due to mercury exposure in hepato-renal injuries. Methods: Research using randomized true laboratory experiment method with post-test control group design. The number of samples used was 28 Wistar rats. The research group consisted of 2 groups, control group was given aquadest ad libitum, and intervention group was given water contaminated with mercury per oral once a day (15 kg/WB). The treatment period was 14 consecutive days and on the 15th day, blood samples were taken. Oxidative stress marker was assessed by examining MDA and GPx levels and hepato-renal injuries were assessed by examining liver function (ALT and AST) and kidney function (ureum and creatinine). The collected data were analyzed by independent t-test with 95% confidence level; significant if p>0.05. Results and Discussion: The study found that mercury can trigger the activation of oxidative stress pathways and have an impact on hepato-renal function. Conclusion: Research still needs to be continued to prove that impaired hepato-renal injuries also occur at the cellular histomorphologic and discover other biomolecular mechanisms such as activation of inflammatory pathways that can also cause organ damage.